(untitled) (Vallis Aurea, 2018)
The energy of each tone of colour has an emotional and psychological effect on an individual which is used as a tool in informal communication. Therefore, when designing new and renovating existing logotypes, designers do not randomly choose colours, but try to convey a certain message with the aim of being recognised. The fact is that colours on a symbol (logo) affect the visual perception and recognisability of individual products, but also of institutions. The paper discusses briefly the history of colour psychology, which is followed by an explanation of the way human eye perceives colour and daltonism. Likewise, we briefly review the application of colour psychology in marketing. After that, the logo of the Cridens Company, part of the Mehun Dental Laboratory, will be presented and explained. Cridens is a company that is engaged in the creation of websites and promotional leaflets, but also comprises a counselling centre for patients of the dental laboratory. The Cridens logo has only two tones of colour, blue and grey, in almost equal proportions. It will be explained in more detail why the company has changed its name and how the newb logo has been designed.